Parametric Study of The Microstrip U-Slot Patch Antenna for Concrete Strength Monitoring - Ngap Chai, Anderson Kho; Then, Yi Lung; Dyg Norkhairunnisa, Abang Zaidel; You, Kok Yeow (2025)
This paper presents a parametric study of a microwave microstrip patch antenna based using finite element modelling software to conduct simulations applied to dielectric material characterization. A probe-fed U-slot patch antenna has been designed to function as a material sensing applicator. The primary objective of this study is to provide non-destructive measurements for predicting the grades of cast concrete in the construction industry. The size, shape, and dimensions of the designed patch antenna are described in detail. The parametric study focuses on the shift in the minimum peak of return loss, |S11| (dB) of the antenna in relation to changes in the dielectric constant of the material under test. The modelling done on the antenna show a significant response in the |S11|, when placed on materials selected to simulate concrete samples at different periods of the curing process, and also at different strength grades. It is known that different strength grades of concrete have varying relative permittivity and dielectric constant values. Consequently, the shift in the minimum peak of the measured |S11| (dB) correlates with changes in concrete strength, thus offering a simple, non-destructive, fast, and effective system for testing concrete quality.